MANAJEMEN PENDIDIKAN UNTUK PENINGKATAN MUTU GURU SEKOLAH DASAR DI SDN WURAN - Ahmad Ridha; Bukhari, Muhammad Ihsan Abadi, Munadinor, Syahrani (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
National education management in Indonesia as a whole still tends to be centralized so that the development of democratization and decentralization of education is not encouraging. Education management problems basically involve efficiency in the use of existing resources. National education management is a strategy that needs to be reorganized to overcome the negative effects of globalization. This management revitalization will also direct globalization in a positive direction for the development of national civilization. So far, the centralized management system of education has proven not to bring significant progress to improving the quality of education in general. In fact, in certain cases, centralized management has hampered the creativity of educational units at various types and levels.